(untitled) (European Journal of Teaching and Education, 2020)
This study uses the data from the Bangladesh Bureau of Statistics, Bangladesh Economic Update, and Bangladesh Export Promotion Bureau to investigate the role of higher education in creating new jobs in Bangladesh. Every year about three million youths are entering job markets. But industry and service sectors do not develop much to provide jobs for such large youth job seekers. This challenge can be faced if universities produce graduates with high level skill and innovative quality. With such graduates Bangladesh can create knowledge-based society and more opportunities will be created for them to get jobs in global markets, and graduates can be successful as entrepreneurs and self-employed workforce. Such dispositions demand changes in curricular, teaching and assessment methods to function young generation as active learners and creators. A simple economic model is used to study the relationship between per capita Gross Domestic Product (GDP) and the three economic sectors, namely agriculture, industry and services sectors for Bangladesh. Using available data both correlation analysis and multiple regression analysis are used to examine the relationship between the dependent variable and the independent variables in the study. The results of this study have implications for economic development policy in Bangladesh.